2022
DOI: 10.1038/s41598-021-04703-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to public health behaviors for fighting COVID-19 derived from longitudinal data

Abstract: The present paper examines longitudinally how subjective perceptions about COVID-19, one’s community, and the government predict adherence to public health measures to reduce the spread of the virus. Using an international survey (N = 3040), we test how infection risk perception, trust in the governmental response and communications about COVID-19, conspiracy beliefs, social norms on distancing, tightness of culture, and community punishment predict various containment-related attitudes and behavior. Autoregre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…The belief in conspiratorial ideas, particularly those involving health-related topics, is widespread [ 56 ]. Conspiratorial beliefs can result in negative consequences by abstaining from adhering to appropriate health behaviors among those endorsing such beliefs [ 45 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The belief in conspiratorial ideas, particularly those involving health-related topics, is widespread [ 56 ]. Conspiratorial beliefs can result in negative consequences by abstaining from adhering to appropriate health behaviors among those endorsing such beliefs [ 45 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…While matters such as polarization and vaccine hesitancy were discussed in the 2020 article and turned out to be clearly relevant, other themes not specified originally were widely studied. For example, political divisions were not the only reasons individuals refused or delayed vaccination 133,134 as there was also evidence of general willful refusal to follow public health guidelines (whether masking, social distancing, isolating when sick, avoiding unnecessary travel, vaccine hesitancy, and so on) in some quarters 135 . In this regard, explicit, manifest behaviors based on demographics and individual differences 136 should also be reviewed as they have not been covered here.…”
Section: Major Behavioral Themes During the Pandemicmentioning
confidence: 99%
“…Previous studies suggested a number of factors that influence the degree to which people in different societies supported or rejected COVID-19 pandemic-related health behaviors, including selfinterest, pro-sociality, religiosity, conspiracy beliefs, trust, national identification, perceived effectiveness, and quality of institutions (7)(8)(9)(10)(11)(12)(13)(14). In this paper, we argue that in order to understand why people support or oppose certain measures, it is crucial to understand (I) which individuals, groups, social movements, or organizations (referred to as 'protagonists' in the following) people identify as relevant and (II) how they are evaluated.…”
Section: Introductionmentioning
confidence: 99%